2008
DOI: 10.1093/jac/dkn051
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in penicillin-binding proteins 1, 2 and 3 are responsible for amoxicillin resistance in Helicobacter pylori

Abstract: Objectives: To elucidate the relationship between the mutations of penicillin-binding protein (PBP)1, PBP2 and PBP3 and amoxicillin resistance in Helicobacter pylori. Methods:The mutations detected only in clinical amoxicillin-resistant strains were determined by comparison of the deduced amino acid sequences of PBP1(HP0597), PBP2(HP1556) and PBP3(HP1565) encoded by the pbp1, ftsI and pbp2 genes, respectively, in 13 clinical H. pylori strains and three ATCC strains. The contribution of the mutations in PBPs wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 10 publications
5
69
1
3
Order By: Relevance
“…The MIC 90 of CLR showed a 128-fold increase after triple therapy with CLR, AMX, and PPI, and the MIC 90 of MNZ showed a 32-fold increase after triple therapy with MNZ, AMX, and PPI (Table 1). While the 23S rRNA point mutation is a main cause of CLR resistance (4) and the single mutation of rdxA or frxA is one of the main causes of MNZ resistance (5), multiple mutations in penicillin binding protein 1 (PBP1) would contribute to a greater increase in the level of AMX resistance (11) and then could result in a gradual increase in AMX resistance.…”
mentioning
confidence: 99%
“…The MIC 90 of CLR showed a 128-fold increase after triple therapy with CLR, AMX, and PPI, and the MIC 90 of MNZ showed a 32-fold increase after triple therapy with MNZ, AMX, and PPI (Table 1). While the 23S rRNA point mutation is a main cause of CLR resistance (4) and the single mutation of rdxA or frxA is one of the main causes of MNZ resistance (5), multiple mutations in penicillin binding protein 1 (PBP1) would contribute to a greater increase in the level of AMX resistance (11) and then could result in a gradual increase in AMX resistance.…”
mentioning
confidence: 99%
“…It should be noted that besides PBP1 changes, there have been a few reports describing changes in outer membrane permeability which have affected amoxicillin susceptibility (4,19), whereas in other reports, only part of the amoxicillin resistance has been attributed to PBP1 changes and the other resistance mechanisms remain uncharacterized (12,13,26,28,29). Finally, Rimbara et al (30) reported that amino acid mutations in PBP2 and PBP3, in concert with although of less consequence than amino acid changes in PBP1, increase amoxicillin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Such a point mutation is able to confer high resistance to all strains in vitro and is considered the main mutation conferring resistance. Other substitutions (Ala369 to Thr, Val374 to Leu, Leu423 to Phe, Thr593 to Ala) not constantly associated with Asn562-Tyr seem to play an additive role in increasing MIC values of the resistant strains similarly to point mutations in PBP2, in PBP3 and PBP4 [48,51] . Interestingly, H. pylori resistant strains obtained by transformation in vitro of susceptible naive strains, exhibit MIC values 5-10 fold lower than naïve resistant strains [49] , suggesting that several and concomitant mechanisms are probably involved in conferring the high levels observed in natural antibiotic resistance.…”
Section: Amoxicillinmentioning
confidence: 94%